2022
DOI: 10.1007/s00227-022-04047-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of carapace composition in developing and adult ostracods (Skogsbergia lerneri) and its potential for biomaterials

Abstract: The protective carapace of Skogsbergia lerneri, a marine ostracod, is scratch-resistant and transparent. The compositional and structural organisation of the carapace that underlies these properties is unknown. In this study, we aimed to quantify and determine the distribution of chemical elements and chitin within the carapace of adult ostracods, as well as at different stages of ostracod development, to gain insight into its composition. Elemental analyses included X-ray absorption near-edge structure, X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated that acidic proteins promote calcium carbonate nucleation when on solid templates and inhibit crystal growth in solution. , In nature, acidic proteins are commonly associated with the biomineralization of carbonates that make up shells, skeletons, and spicules. ,, Aspartic acids in particular were shown to modify calcite crystal morphology by altering the surface energy at certain crystallographic facies. , As a consequence, aspartic acid exerts a strong influence on crystal morphology . Chitin also wields a significant influence on ACC and calcium carbonate growth. , Chitin is known to be widespread in biocalcifiers and likely contributes to the formation of calcium carbonates in coralline algae, , crustaceans, ostracods, and mollusks . Laboratory experiments have also demonstrated that chitin has the ability to promote heterogeneous nucleation of calcite at room temperature without the presence of magnesium. , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that acidic proteins promote calcium carbonate nucleation when on solid templates and inhibit crystal growth in solution. , In nature, acidic proteins are commonly associated with the biomineralization of carbonates that make up shells, skeletons, and spicules. ,, Aspartic acids in particular were shown to modify calcite crystal morphology by altering the surface energy at certain crystallographic facies. , As a consequence, aspartic acid exerts a strong influence on crystal morphology . Chitin also wields a significant influence on ACC and calcium carbonate growth. , Chitin is known to be widespread in biocalcifiers and likely contributes to the formation of calcium carbonates in coralline algae, , crustaceans, ostracods, and mollusks . Laboratory experiments have also demonstrated that chitin has the ability to promote heterogeneous nucleation of calcite at room temperature without the presence of magnesium. , …”
Section: Discussionmentioning
confidence: 99%
“…46 Chitin also wields a significant influence on ACC and calcium carbonate growth. 47,48 Chitin is known to be widespread in biocalcifiers and likely contributes to the formation of calcium carbonates in coralline algae, 49,50 crustaceans, 51 ostracods, 52 and mollusks. 53 Laboratory experiments have also demonstrated that chitin has the ability to promote heterogeneous nucleation of calcite at room temperature without the presence of magnesium.…”
Section: Mineralogy Of Synthetic Ca−mg Carbonate Precipitates In Solu...mentioning
confidence: 99%